2016
DOI: 10.1016/j.ijnurstu.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Parent education interventions designed to support the transition to parenthood: A realist review

Abstract: It is unlikely that a single standardized format or programme will meet all the specific learning needs of parents. Multiple approaches that will allow people to access information or education at a time and in a format that suits them may be of value. The importance of the transition to parenthood and its impact on parent and child wellbeing warrant careful consideration of current programming and careful evaluation of future initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 78 publications
(88 reference statements)
4
78
0
6
Order By: Relevance
“…This could be due to personality traits but could also be due to a competitive group climate as described by some fathers. Although parental preparation sessions may be one method, there appears to be a call for differing types of pedagogical approaches to parenthood preparation, a finding corroborated by earlier research (Gilmer et al 2016). The idea presented by fathers in the present study, of learning from other new parents was also shown in a review of the literature by Entsieh and Hallström (2016) and the encouraging effect of support from both peers and family is previously well known (Deave et al, 2008;Svensson et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
“…This could be due to personality traits but could also be due to a competitive group climate as described by some fathers. Although parental preparation sessions may be one method, there appears to be a call for differing types of pedagogical approaches to parenthood preparation, a finding corroborated by earlier research (Gilmer et al 2016). The idea presented by fathers in the present study, of learning from other new parents was also shown in a review of the literature by Entsieh and Hallström (2016) and the encouraging effect of support from both peers and family is previously well known (Deave et al, 2008;Svensson et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
“…lack of evidence ( n  = 3): according to the review authors, it was difficult to evaluate the quality of evidence in the studies they analysed because either the methodological rigour was considered poor [43], it could not be objectivised [44] or there was no description of the intervention’s content, implementation or results [45]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, health promotion stakeholders seem to assume a lack of parental skills. Parental knowledge should be evaluated prior to the intervention [45]. Finally, the value of peer groups is an under-researched area [30] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations